The impact of physicochemical properties of coal on direct carbon solid oxide fuel cells. (2nd November 2016) - Dudek, Magdalena; Skrzypkiewicz, Marek; Moskała, Norbert; Grzywacz, Przemysław; Sitarz, Maciej; Lubarska-Radziejewska, Iwona
Abstract: Two different coals were investigated, both before and after purification with inorganic acids, as solid fuels in a direct carbon solid oxide fuel cell (DC-SOFC). Prior to electrochemical investigations, elemental and technical analyses of both raw and purified coal samples were performed. It was found that the applied purification process considerably reduced the total amount of sulphur and mineral matter in the investigated coals. The phase composition of mineral matter in ash was also analysed, using the X-ray diffraction method as well as infrared spectroscopy. The reactivity of these coals in a CO2 atmosphere was investigated. It was found that the purified coal samples exhibited greater chemical reactivity than pure carbon black samples. The electrochemical oxidation of the raw and purified coal samples was investigated at a temperature range of 600–850 °C on the surface of an 8YSZ electrolyte. Lower values of current density and power were acquired from a DC-SOFC supplied with powdered coal containing higher amounts (8 wt.%) of mineral matter compared to coal with 4 wt.%. It was found that negative impact of silica and kaolinite contained in the former sample exceeded that expected from a sample containing 6 wt% of mineral matter on the process of electrochemical oxidation on the 8YSZ and Ni-YSZ surface. An improvement was observed in the performance of a DC-SOFC with a Ni-YSZ anode due to the presence of additional CO from the gasification of coals within the DC-SOFC. Highlights: Two coals prior to purification (4 and 8 wt% ash) and after (0.5 and 1.5 wt% ash) were applied as solid fuels in DC-SOFCs. The presence of ash in coal higher than 6 wt% led to a decrease in the performance of the DC-SOFC. Differences in the physicochemical properties of coal and mineral matter are reflected by the efficiency of the gasification process as well as the power output in DC-SOFCs. Coal samples involving an inorganic matter in the range 2–5 wt% and organic sulphur content not higher than 0.1 wt% seem to be valuable solid fuels. The power output of the DC-SOFC supplied by purified coals was approximately 100 mW/cm 2 .